Preliminary Design Of Butyl Oleate Plantfromoleic Acid And Butanolcapacity 15,000 Tons/Year - PRANOTO, Agung Dwi; , Ir. Nur Hidayati, M.T., Ph.D; , Emi Erawati, S.T., M.Eng (2014)
Chemical plantof Butyl oleate from Oleic acid and Butanol as raw material with a capacity of 15,000 tons per year is planned to operate for 330 days per year. Butyl oleate-production process is carrie out in a Continuous Stirred Reactor Tank (CSTR) with liquidphasecatalyticesterificationwithH2SO4. In the reactor the reaction takes place in the liquid-liquid phase, reversible, exothermic, nonadiabatic and isothermal at 110oC temperature and pressure of 1 atm. This plant is classified as a low risk because of it moderateoperating conditions of atmospheric and easy product sales. Oleic acid requirement for this plant is1532.29 kg per hour and needs butanolis 450.12 kg per hour to produce butyl oleate is 1893.94 kg per hour. The plant was planned establishedin Gresik, EastJava with a land area of 20.000 m2.The selection of location due to some consideration, i.e,asraw material ofbutyloleateplant,butanol,to be importedfromthe United Statesand ,oleic acid,imported fromAustraliathroughthe port of TanjungPerak. Whilesulfuricacidraw materialfromPT.SulfindoAdiusahaandsodiumhydroxidewas purchasedfromPT.Sidowaru.The number of employees 110 people.Utilities supporting processes include water supply of 5,605.24 kg per hour which are processed from Bengawan Solo River, provision of saturated steam per hour 1,567.04 kg. The plant's electricity needs of 500kW, in the form of diesel fuel requirements of 238.1 liters/hour, and the need for compressed air for instrumentation of 50 m3/h. Chemical plantof Butyl oleat using fixed capital as much as Rp 369,418,206,279.36and working capital as much as Rp141,928,507,967.97.From the economic analysis of this plant showed a profit before tax of Rp84,782,608,336per year and after taxes 30% profit reachedRp59,347,825,835 per year. Percent Return On Investment (ROI) before tax 22.95% and 16.07% after tax. Pay Out Time (POT) before tax 3.03 years and after tax 3.84 years. Break Even Point (BEP) of 53.9%, and Shut Down Point (SDP) of 27.92%. Discounted Cash Flow (DCF) as much as 38%. From the data above feasibility analysis concluded that the plant is profitable and feasible to set up